On the strong law for arrays and for the bootstrap mean and variance - Tien-Chung Hu; R. L. Taylor (International Journal of Mathematics and Mathematical Sciences, 1997)
Chung type strong laws of large numbers are obtained for arrays of rowwise independent random variables under various moment conditions. An interesting application of these results is the consistency of the bootstrap mean and variance.